The conditions of security in sustainable rural economics - Elekes , Edit (Applied Studies in Agribusiness and Commerce, 2014)
This work aims to map the potentials of safe rural economy. This topic cannot be separated from the processes of globalization and localization, affecting each other, whose positive and negative effects have been focussed on, especially in terms of the protection of security and sustainability or their damaging. In Hungary, sustainable rural economy cannot be achieved only by the rural economy’s systematic stabilization but its present structure and the security system, accompanying the process, also needs to undergo some drastic changes. Sustainable rural economy means a modern economy that aims to keep the rural inhabitants while increases the wealth of the whole society. The legal security of the sustainable local economy is guaranteed by the state in Hungary. The security of the rural areas is provided by the police as an armed force, the auxiliary police, the public place supervision, the local agricultural rangers, the environment wardens, and by the fish- and game-keepers. The Police Act allows cooperation with the further organizations of the society to preserve public order, and to protect property and prevent and detect crimes. The purpose of my thesis is to present security as one of the most important factors to improve the rural areas. I also aim to map the possibilities of improving security (such as cooperation, naming the resources assisting strategic tenders and participation in rural development programs).